2013
DOI: 10.1155/2013/621095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thermal Mass, Window Size, and Night‐Time Ventilation on Peak Indoor Air Temperature in the Warm‐Humid Climate of Ghana

Abstract: Most office buildings in the warm-humid sub-Saharan countries experience high cooling load because of the predominant use of sandcrete blocks which are of low thermal mass in construction and extensive use of glazing. Relatively, low night-time temperatures are not harnessed in cooling buildings because office openings remain closed after work hours. An optimization was performed through a sensitivity analysis-based simulation, using the Energy Plus (E+) simulation software to assess the effects of thermal mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 10 publications
0
14
1
1
Order By: Relevance
“…The studies carried out by Artmann, Manz and Heiselberg (2008) showed that appropriate selection of window type can contribute to reducing overheating degree hours by controlling the air speed and direction. In another study, Amos-Abanyie, Akuffo, and Kutin-Sanwu (2013) revealed that combining application of effective window size, NTV and thermal mass can reduce the peak indoor temperature and improve thermal comfort in a warm-humid context. The required percentage of the effective window opening may vary depending on the outdoor weather conditions and heat gain from occupants (Lomas 2007).…”
Section: Changing Window Type and Effective Opening Sizementioning
confidence: 99%
See 1 more Smart Citation
“…The studies carried out by Artmann, Manz and Heiselberg (2008) showed that appropriate selection of window type can contribute to reducing overheating degree hours by controlling the air speed and direction. In another study, Amos-Abanyie, Akuffo, and Kutin-Sanwu (2013) revealed that combining application of effective window size, NTV and thermal mass can reduce the peak indoor temperature and improve thermal comfort in a warm-humid context. The required percentage of the effective window opening may vary depending on the outdoor weather conditions and heat gain from occupants (Lomas 2007).…”
Section: Changing Window Type and Effective Opening Sizementioning
confidence: 99%
“…The studies carried out by Artmann, Manz and Heiselberg (2008) showed that appropriate selection of window type can contribute to reducing overheating degree hours by controlling the air speed and direction. In another study, Amos-Abanyie, Akuffo, and Kutin-Sanwu (2013) revealed that combining application of effective window size, NTV and thermal mass According to International Labour Organisation Action Manual (1998), thermal comfort in RMG factories where air is supplied from the sides depends on the uniformity of indoor air speed and reduction of AT in the production spaces. In this study, therefore, flexible configuration of windows with the higher effective opening area was considered as one of the key design strategies for improving the thermal condition in RMG factories.…”
Section: Changing Window Type and Effective Opening Sizementioning
confidence: 99%
“…A gap exists in literature on practical data of thermo-physical properties of materials used as envelope in buildings in the Sub-Saharan countries [10]. Several factors such as surface area, thickness, thermal transmittance, among others influences heat transfer into building envelope.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the high outdoor air humidity, about 95% in summer, is another reason. These two reasons lead to a decline in the coefficient of performance (COP) of most air cooled units to the range of 2.2-2.4 [3].…”
Section: Introductionmentioning
confidence: 99%